Fine-scale genetic structure of Triatoma infestans in the Argentine Chaco - Piccinali, Romina Valeria (2015)
The patterns of genetic structure in natural populations provide essential information for the improvement of pest management strategies including those targeting arthropod vectors of human diseases. We analyzed the patterns of fine-scale genetic structure in Triatoma infestans in a well-defined rural area close to Pampa del Indio, in the Argentine Arid-Humid Chaco transition, where a longitudinal study on house infestation and wing geometric morphometry is being conducted since 2007. A total of 228 insects collected in 16 domestic and peridomestic sites from two rural communities was genotyped for 10 microsatellite loci and analyzed. We did not find departures from Hardy–Weinberg expectations in collection sites, with three exceptions probably due to null alleles and substructuring. Domestic sites were more variable than peridomestic sites suggesting the presence of older bug populations in domestic sites or higher effective population sizes. Significant genetic structure was detected using F-statistics, a discriminant analysis of principal components and Bayesian clustering algorithms in an area of only 6.32 km2 . Microsatellite markers detected population structuring at a finer geographic scale (180–6300 m) than a previous study based on wing geometric morphometry (>4000 m). The spatial distribution of genetic variability was more properly explained by a hierarchical island than by an isolation-by-distance model. This study illustrates that, despite more than a decade without vector control interventions enhancing differentiation, genetic structure can be detected in T. infestans populations, particularly applying spatial information. This supports the potential of genetic studies to provide key information for hypothesis testing of the origins of house reinfestation.